Helping skills facilitating exploration, insight, and action - Hill, Clara E. 1948-; O'Brien, Karen M. (American Psychological Association, 1999)
This book presents a three-stage model of helping, grounded in 25 years of research, that can be used to assist individuals who are struggling with emotional or transitional difficulties. To master the skills they need to lead clients through the Exploration, Insight, and Action stages, students are given both theoretical guidance and opportunities for formulating solutions to hypothetical clinical problems. Grounded in client-centered, psychoanalytic, and cognitive-behavioral theory, this book offers an integrative approach. Tables and lists supplement the text, along with clinical examples.--From publisher's description.